Pengaruh Kepemimpinan, Kepuasaan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) Pegawai Kantor Pertanahan Kabupaten Bireuen - Wijayanti, Enik; Yusuf, M.; Danil, Mahyu (Singkite Journal, 2024)
This research was proposed to find out how much influence Leadership, Job Satisfaction and Organizational Commitment have on the Organizational Citizenship Behavior of Bireuen Regency Land Office Employees. The data collection method used in this research was by administering questionnaires to 46 respondents at the Bireuen Regency Land Office. Data collection techniques through open interviews, questionnaires and supporting documentation.  The analysis technique in this research uses multiple linear regression analysis. The research results show that the independent variable simultaneously has a significant influence on the dependent variable. Variables consisting of Leadership, Job Satisfaction and Organizational Commitment partially and simultaneously influence the Organizational Citizenship Behavior of Bireuen Regency Land Office employees